Age-related differences in long-term potentiation-like plasticity and short-latency afferent inhibition and their association with cognitive function - Tong Wang; Ying Shen; Tianjiao Zhang; Chuan He; Qian Lu; Jie Song; Manyu Dong; Yilun Qian; Sisi Huang; Jing Teng (General Psychiatry)
Background The neurophysiological differences in cortical plasticity and cholinergic system function due to ageing and their correlation with cognitive function remain poorly understood.Aims To reveal the differences in long-term potentiation (LTP)-like plasticity and short-latency afferent inhibition (SAI) between older and younger individuals, alongside their correlation with cognitive function using transcranial magnetic stimulation (TMS).Methods The cross-sectional study involved 31 younger adults aged 18–30 and 46 older adults aged 60–80. All participants underwent comprehensive cognitive assessments and a neurophysiological evaluation based on TMS. Cognitive function assessments included evaluations of global cognitive function, language, memory and executive function. The neurophysiological assessment included LTP-like plasticity and SAI.Results The findings of this study revealed a decline in LTP among the older adults compared with the younger adults (wald χ2=3.98, p=0.046). Subgroup analysis further demonstrated a significant reduction in SAI level among individuals aged 70–80 years in comparison to both the younger adults (SAI(N20): (t=−3.37, p=0.018); SAI(N20+4): (t=−3.13, p=0.038)) and those aged 60–70 (SAI(N20): (t=−3.26, p=0.025); SAI(N20+4): (t=−3.69, p=0.006)). Conversely, there was no notable difference in SAI level between those aged 60–70 years and the younger group. Furthermore, after employing the Bonferroni correction, the correlation analysis revealed that only the positive correlation between LTP-like plasticity and language function (r=0.61, p<0.001) in the younger group remained statistically significant.Conclusions During the normal ageing process, a decline in synaptic plasticity may precede cholinergic system dysfunction. In individuals over 60 years of age, there is a reduction in LTP-like plasticity, while a decline in cholinergic system function is observed in those over 70. Thus, the cholinergic system may play a vital role in preventing cognitive decline during normal ageing. In younger individuals, LTP-like plasticity might represent a potential neurophysiological marker for language function.